POST COVID-19 SYNDROME EFFECT ON DAILY LIFE ACTIVITIES - Sianty Dewi; Bernadette Dian Novita Dewi; Niluh Suwasanti; Paul L Tahalele; Evelyn Ongkodjojo; Wilson Christianto Khudrati; Kevin Samsudin; Ni Nyoman Ratih Dharmapatni; Delvi Vorst; Theresia Cindy Limantoro (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
The Covid-19 pandemic had a big impact on the world over the past two years., and it is estimated that 1 in 10 people have been infected. The development of prevention and treatment systems can reduce mortality, but a new problem has emerged in the group of survivors. New clinical complaints, Getting COVID-19 again or having ongoing symptoms of COVID-19 for four weeks after the first infection, can affect a wide variety of organ functions. The long-term effects of having COVID-19, like feeling tired, having trouble breathing, chest pain, difficulty thinking, and joint pain, can make life worse. The study was conducted using a qualitative descriptive method using an online questionnaire. The results showed that some residual symptoms that respondents still felt after four weeks since being infected with COVID-19, such as fatigue easily (80%), joint pain (63.3%), insomnia (56.7%), depressive symptoms (53.3%), shortness of breath (50%), impaired concentration and memory (50%), livelihood disorders (43.3%), cough (40%), respiratory disorders (36.7%), weight loss and appetite (33.3%), fever (26.7%). Overall, it was found that 20% of COVID-19 survivors experienced daily activity disruptions assessed using the Modifications of Barthel Index and EQ-5D-5L questionnaires.